Participatory Empowerment: Enhancing Rural Coffee Shop Competitiveness through Innovation and Digital Marketing - Dhanny Safitri; Ni Putu Inten Nindya Paramitha; Fety Widianti Aptasari; Baiq Krisnina Maharani Putri; Dinis Cahyaningrum; Khairul Mujahidi (Westscience Press, 2026)
This community service program addresses the challenges faced by rural coffee MSMEs in Indonesia’s hyper-competitive market, specifically focusing on Empati Kopi in West Lombok. Many rural businesses struggle with digital literacy gaps and limited product innovation, which hinders their ability to compete with larger franchises. Utilizing a participatory empowerment approach, the program engaged the owner and staff through situational analysis, collaborative planning, and intensive mentoring. The results demonstrate significant improvements in product innovation, including the development of new beverage variants and refined packaging that strengthened the shop’s brand identity. While basic digital marketing practices were successfully introduced to improve online visibility, participants continued to encounter challenges in producing high-quality visual content and maintaining consistent digital engagement. The program reveals that while product-based improvements can be effectively implemented through short-term interventions, mastering digital marketing requires continuous technical assistance. Ultimately, this initiative fostered greater entrepreneurial confidence, demonstrating that tailored empowerment strategies are vital for sustaining rural MSMEs in a digital economy.